ABCA7 loss-of-function variants, expression, and neurologic disease risk. (February 2017) - Allen, Mariet; Lincoln, Sarah J.; Corda, Morgane; Watzlawik, Jens O.; Carrasquillo, Minerva M.; Reddy, Joseph S.; Burgess, Jeremy D.; Nguyen, Thuy; Malphrus, Kimberly; Petersen, Ronald C.; Graff-Radford, Neill R.; Dickson, Dennis W.; et al.
Abstract : Objective: To investigate and characterize putative "loss-of-function" (LOF) adenosine triphosphate–binding cassette, subfamily A member 7 ( ABCA7 ) mutations reported to associate with Alzheimer disease (AD) risk. Methods: We genotyped 6 previously reported ABCA7 putative LOF variants in 1, 465 participants with AD, 381 participants with other neuropathologies (non-AD), and 1, 043 controls and assessed the overall mutational burden for association with different diagnosis groups. We measured brain ABCA7 protein and messenger RNA (mRNA) levels using Western blot and quantitative PCR, respectively, in 11 carriers of the 3 most common variants, and sequenced all 47 ABCA7 exons in these participants to screen for other coding variants. Results: At least one of the investigated variants was identified in 45 participants with late-onset Alzheimer disease, 12 participants with other neuropathologies, and 11 elderly controls. Association analysis revealed a significantly higher burden of these variants in participants with AD ( p = 5.00E-04) and those with other neuropathologies ( p = 8.60E-03) when compared with controls. Concurrent analysis of brain ABCA7 mRNA and protein revealed lower protein but not mRNA in p.L1403fs carriers, lower mRNA but not protein in p.E709fs carriers, and additional deleterious mutations in some c.5570+5G>C carriers. Conclusions: Our results suggest that LOF may not be a common mechanism for these ABCA7 variants and expand the list of neurologic diseases enriched for them.